The management of grassland areas for wintering geese - Owen, Myrfyn (Wildfowl, 1973)
Basic management policies for semi-natural and agricultural grassland to improve them as goose habitats are set out. Disturbance is the most important single factor, and various types are listed and their relative importance considered. A relatively objective ’avoidance index’ was computed, which showed a negative correlation coefficient greater than 0.8 with actual goose usage over four seasons. The presence of standing water, at which they can drink, preen and bathe, on the feeding grounds is beneficial to grazing geese in midwinter when up to 95% of their daytime must be spent feeding. The quantity of grass in winter is affected by farm stock grazing pressure in autumn and early winter. The quantity of clover stolons, another important goose food, on salting pasture increases as summer stock grazing pressure, which affects vegetation height, increases. The selection of feeding sites and food by Whitefronts was shown to be in part determined by the nutritional quality of that food. Quality can be increased by proper summer grazing management, cutting, fertilizing and reseeding.